Pernicious Patriarchy or Prosecutorial Progress?:: Confronting Culture, War, and Rape in International Law - Zeigler, Sara; Gunderson, Gregory (Journal of Conflict Studies, 2005)
ABSTRACT In the aftermath of the wars in the former Yugoslavia, feminist activists have encouraged the use of international law to prosecute those leaders employing rape as a tool for ethnic cleansing. First, we will analyze the reasons that rape is effective in disrupting social and against women. Second, we will elucidate the peculiar problems of prosecuting war criminals whose offenses targeted female non-combatants in the form of sexual violence. We begin with an examination of the international law related to war crimes, as well as the ethical implications of various techniques used to enforce the law and bring war criminals to justice. A brief examination of key areas of US rape law will demonstrate the relative leniency extended to perpetrators of violence against women domestically in a nation that guarantees women full juridical equality. After examining some specific prosecutions, we will apply the lessons learned to the larger context of international law.